Hubungan Antara Hasil Pemeriksaan Sputum BTA dengan Hasil Resistensi Rifampisin Genexpert MTB/RIF di RSUD Doris Sylvanus Tahun 2018-2019: Relationship Between BTA Sputum Examination Results and Geneexpert MTB/RIF Rifampicin Resistance Results at Doris Sylvanus Hospital in 2018-2019 - Silvani Permatasari; Dea Tutut; Dewi Klarita Furtuna; Florence Felicia; Fraulein Aryati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: Tuberculosis (TB) is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. The sputum Acid-Fast Bacillus (AFB) examination is a widely used diagnostic test, but it is difficult to control a minimum of 5,000 germs / ml of sputum to get a positive result. The GeneXpert MTB / RIF examination is an automatic machine with easy and fast use that uses the principle of real-time nested PCR and molecular technology for the examination of Mycobacterium tuberculosis (MTB) and rifampicin resistance (RR). Purpose: To determine the relationship between the results of sputum AFB examination and the results of rifampicin resistance GeneXpert MTB / RIF in pulmonary TB patients at Doris Sylvanus Hospital, Palangka Raya for the period 2018-2019. Methods: This study used an analytic observational method with a cohort study design. The subjects of this study were all pulmonary TB patients who had been examined for sputum AFB and GeneXpert MTB / RIF at Doris Sylvanus Regional Hospital for the period 2018-2019. Data analysis used SPSS program with Chi Square test (p <0.05). Results: The results of statistical tests showed that the Sputum BTA result variable had a significant relationship with the GeneXpert MTB / RIF outcome variable. So the result is p = 0.009. Conclusion: There is a significant relationship between the results of sputum AFB examination and the results of rifampicin resistance of GeneXpert MTB / RIF in pulmonary TB patients at Doris Sylvanus Hospital, Palangka Raya for the period 2018-2019.